IMPLEMENTASI APLIKASI INFORMASI PELAYANAN KESEHATAN PADA RSUD OTO ISKANDAR DI NATA KABUPATEN BANDUNG - Kastaman, Kastaman; Yuniar, Irna; Mayadewi, RA Paramita; Anshori, Abdul Matin (LPPM Universitas Bina Bangsa, 2024)
Hospitals must provide information that is complete, easy to understand, and accessible to all members of the community to provide the best service. Newly-arrived hospital patients usually feel confused by health care facilities. Limited personnel resources in hospitals that serve many visitors may contribute to poor service. A large number of visitors can reduce the quality of service. This will make visitors dissatisfied with the service. Complaints experienced by visitors in various hospitals include long service times to completion, complaints about administrative problems, communication and attitude of officers, unclear information on handling complaints, handling complaints that are considered too complicated a process, no solution to complaints, perceived discriminatory and unfair health services, and unclear information on costs borne by patients. The solution and output target of this Community Service activity is to provide products and services for the application of health service information applications. With the application of this application, it is hoped that it can be used to help the effectiveness of the performance they carry out daily and is useful for improving facility management to produce detailed and relevant information